Research status of Chinese medicine formula based on network pharmacology - Zhenghui Pan; Mengqian Li; Zhiyu Jin; Ding Sun; Danshen Zhang; Beibei Hu; Zhongqiu Li; Yongshuai Jing; Shiguo Sun (Elsevier, 2022)
Traditional Chinese Medicine (TCM) has some advantages, such as a multi-component, multi-target, and overall action, which makes the research on the compatibility of TCM formula a key and difficult point. On the contrary, network pharmacology (NP) uses high-throughput screening, computer simulation, and network database retrieval to reveal the drug-gene-target-disease interaction network, predict the mechanism of action of drugs through network relationships, and evaluate the efficacy and adverse reactions of drugs, thereby determining drugs with high efficiency and low toxicity. Therefore, the TCM formula has its unique TCM theories, and this paper primarily introduces the status quo of TCM compound prescriptions using TCM theories and NP, namely, the treatment theory of TCM (the core of TCM treatment and the principle of compatibility of TCM), as the theoretical guidance to evaluate drug's properties, efficacy, and toxicity. In addition, this study aims to predict drug's mechanism of action, interaction relationship, and matching selection to provide a high-efficiency and low-toxicity TCM formula and new insights into the follow-up study of TCM formula.